Assessment of critical success factors of business process re-engineering in the Nigerian oil and gas industry - U. O. Asikhia; D. O. Awolusi (South African Journal of Business Management, 2015)
Business Process Re-engineering (BPR) is defined as the critical analysis and radical redesign of existing business processes to achieve breakthrough improvements in performance measures like cost, quality, speed, profitability and services. The purpose of this paper is to identify the critical success factors of BPR implementation, to evaluate their effects on the primary measures as expressed by the operational performance and the secondary measures as expressed by the organizational performance, and to find out the effect of the operational performance on the organizational performance of Nigerian oil and gas companies. To achieve these objectives, an empirical study was conducted via the administration of 650 self-administered copies of questionnaire to a randomly selected senior and management staff of eight (8) re-engineered Oil and Gas Companies in Nigeria. Using the framework from Khong Richardson (2003), factors manifesting operational performance and organizational performance were regressed on the Critical Success Factors (CSFs) manifesting successful BPR. Findings based on the survey revealed that successful BPR can positively affect both operational and organizational performance measures in the Nigerian oil and gas companies.
Keywords: 650